2006
DOI: 10.1093/hmg/ddl104
|View full text |Cite
|
Sign up to set email alerts
|

Association of PINK1 and DJ-1 confers digenic inheritance of early-onset Parkinson's disease

Abstract: Mutations in genes encoding both DJ-1 and pten-induced kinase 1 (PINK1) are independently linked to autosomal recessive early-onset familial forms of Parkinson's disease (PD). We here report identification of a family with PD patients harboring novel heterozygous missense mutations in both PINK1 and DJ-1 genes encoding DJ-1A39S and PINK1P399L, respectively. In transfected cells, DJ-1 interacts with PINK1. PINK1P399L is less stable than the wild-type protein and is degraded via the ubiquitin-mediated proteasoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(152 citation statements)
references
References 50 publications
10
141
0
1
Order By: Relevance
“…Functional studies suggest that wildtype PINK1 may have a neuroprotective role (4) that is abrogated by pathogenic mutations in the PINK1 gene. Consistent with the notion, we have recently shown that PINK1 and DJ-1 physically associate and collaborate to protect cells against oxidative stress (15). These results suggest a potential role of PINK1 in maintaining mitochondrial homeostasis and in defending against oxidative stress.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Functional studies suggest that wildtype PINK1 may have a neuroprotective role (4) that is abrogated by pathogenic mutations in the PINK1 gene. Consistent with the notion, we have recently shown that PINK1 and DJ-1 physically associate and collaborate to protect cells against oxidative stress (15). These results suggest a potential role of PINK1 in maintaining mitochondrial homeostasis and in defending against oxidative stress.…”
supporting
confidence: 80%
“…In vitro, parkin and DJ-1 have been shown to protect cells from oxidative stress (26)(27)(28)(29)(30)(31). Moreover, PINK1 interacts with DJ-1 and digenic mutations of PINK1 and DJ-1 are associated in early onset familial form of PD (15). Consistent with our findings that antioxidants can ameliorate the dPINK1-dependent PD pathology in Drosophila are two recent reports that show that deletion mutants of dPINK1 result in abnormally functioning mitochondria, sensitization to oxidative stress, and mild degeneration of DA neurons (32,33).…”
Section: Aј-dј and E)mentioning
confidence: 99%
“…14-3-3E is a member of the 14-3-3 family of phosphoserine-binding adapter molecules that mediate a general survival-promoting function through interaction with target proteins, by enhancing pro-survival signalling while suppressing activity of proapoptotic proteins (Porter et al, 2006). PINK1 encodes a Ser/ Thr kinase with a mitochondrial-targeting signal, and acts with DJ-1 to protect cells against oxidative stress-induced cell death (Tang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, a recent study reports that digenic mutations of PINK1 and DJ-1 are associated with early-onset familial PD cases (10). In addition, expression of these two pathogenic proteins potentiates susceptibility of SH-SY5Y cells to oxidative stress, and PINK1 and DJ-1 can form a complex when coexpressed in mammalian cells (10). PINK1 and DJ-1 appear to function in the same pathway as Parkin, which encodes an E3 ubiquitin ligase that is thought to function primarily in the cytoplasm, presumably to target specific protein targets for degradation or modified function͞local-ization (11).…”
Section: The Parkinson Pathwaymentioning
confidence: 59%
“…PINK1 is likely to function in conjunction with another mitochondrial protein known as DJ-1 because mutations in this gene also cause autosomal recessive forms of PD. Consistent with this notion, a recent study reports that digenic mutations of PINK1 and DJ-1 are associated with early-onset familial PD cases (10). In addition, expression of these two pathogenic proteins potentiates susceptibility of SH-SY5Y cells to oxidative stress, and PINK1 and DJ-1 can form a complex when coexpressed in mammalian cells (10).…”
Section: The Parkinson Pathwaymentioning
confidence: 80%